Classical Javanese Literature Wulangreh From Surakarta Palace: Study Of Islamic Tourism - Esti - Ismawati; Warsito Warsito; Kun Andyan Anindita (The Pontianak State Institute of Islamic Studies, 2022)
Classical Javanese literary works have many variations, one of which is the work entitled Wulangreh (teaching with dedication) written by King Pakubuwana IV of the Surakarta palace when Indonesia was still under Dutch colonial rule. This study aims to describe the beauty of universal Islamic cultural values in this book, which was published in the 18th century but is still being used today. The question answered is, are the universal cultural values in the book still relevant today? What values attract tourists to come and learn about them? The research method used is descriptive qualitative with a hermeneutic approach triangulated with the opinion of cultural experts. The data was obtained by interpreting the thoughts of King Pakubuwana IV written in the book and interviews with Kanjeng Yusdianto, a traditional leader of the Surakarta palace and the head of the Radya Pustaka museum, Didik Suharjono. The results of the analysis show that the values in the book can be a reference for the world because of their universal nature, including the values of equality, multiculturalism, and civilization. The beauty of the language and the message conveyed by the King is very touching, especially if tourists want to come to Surakarta to see directly Wulangreh, the tomb of King Pakubuwana IV, the Radya Pustaka museum, and the Surakarta Palace. The religious and cultural values of Islam in the book can be used as provisions for readers in facing life today. Wulangreh, Pakubuwana IV Tomb, Surakarta Palace, and Radya Pustaka Museum are icons of religious and cultural tourism destinations in the recommended Era 5.0.